2017
DOI: 10.21037/jtd.2017.06.15
|View full text |Cite
|
Sign up to set email alerts
|

Short-term high-intensity rehabilitation in radically treated lung cancer: a three-armed randomized controlled trial

Abstract: Background:The feasibility and practicality of preoperative rehabilitation (PR) programs remains quite controversial in the treatment of lung cancer (LC). This study explored whether a short-term high-intensity rehabilitation program could improve postoperative outcomes compared to those achieved with conventional inspiratory muscle training (IMT).Methods: A three-armed randomized controlled trial comparing the two training modalities and routine care was conducted in surgical LC patients. Patient groups recei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
134
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 69 publications
(135 citation statements)
references
References 27 publications
1
134
0
Order By: Relevance
“…33,34 A randomized controlled trial in patients with lung cancer undergoing short-term intensive rehabilitation prior to radical surgery showed positive results, with a significant decrease in hospital stay after surgery. 35 However, most current trials are small; larger randomized controlled trials should clarify whether a multimodal rehabilitation program can reduce the negative effects of low SMM in patients undergoing TL. Alternatively, treatment planning could take the low SMM into account.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…33,34 A randomized controlled trial in patients with lung cancer undergoing short-term intensive rehabilitation prior to radical surgery showed positive results, with a significant decrease in hospital stay after surgery. 35 However, most current trials are small; larger randomized controlled trials should clarify whether a multimodal rehabilitation program can reduce the negative effects of low SMM in patients undergoing TL. Alternatively, treatment planning could take the low SMM into account.…”
Section: Discussionmentioning
confidence: 99%
“…Feasibility studies in patients with HNC have shown that resistance training programs in patients undergoing chemoradiotherapy or radiotherapy are feasible and show high patient satisfaction . A randomized controlled trial in patients with lung cancer undergoing short‐term intensive rehabilitation prior to radical surgery showed positive results, with a significant decrease in hospital stay after surgery . However, most current trials are small; larger randomized controlled trials should clarify whether a multimodal rehabilitation program can reduce the negative effects of low SMM in patients undergoing TL.…”
Section: Discussionmentioning
confidence: 99%
“…The institutional policies for perioperative care, including the preoperative pulmonary rehabilitation, postoperative pain control, lung recruitment assessment and postoperative chest tube management had been reported in our previous studies (2,4,5,15,16).…”
Section: Surgical Procedure Perioperative Care and Discharge Criteriamentioning
confidence: 99%
“…After surgery, patients were managed in compliance with a standardized clinical pathway. The institutional policies for intensive pulmonary rehabilitation, residual lung recruitment assessment, chest tube management, and discharge criteria, have been reported in our previous studies …”
Section: Methodsmentioning
confidence: 99%
“…The institutional policies for intensive pulmonary rehabilitation, residual lung recruitment assessment, chest tube management, and discharge criteria, have been reported in our previous studies. 6,12,13,[21][22][23][26][27][28][29] An algorithm of chylothorax management is shown in Figure 1. Once diagnosed with chylothorax, patients were initially managed with oral intake cessation (OIC) and total parenteral nutrition (TPN).…”
Section: Surgical Procedures and Perioperative Carementioning
confidence: 99%